Crystal structure of (E)-3-allyl-2-sulfanylidene-5-[(thiophen-2-yl)methylidene]thiazolidin-4-one - El Ajlaoui, Rahhal (Acta Crystallogr E Crystallogr Commun, 2015)
Molecules of the title compound, C(11)H(9)NOS(3), are built up by one thiophene and one 2-thioxathiazolidin-4-one ring which are connected by a methylene bridge. In addition, there is an allyl substituent attached to nitrogen. The two rings are almost coplanar, making a dihedral angle between them of 0.76 (11)°. The allyl group is oriented perpendicular to the mean plane through both ring systems. The crystal structure exhibits inversion dimers in which molecules are linked by pairs of C—H⋯O hydrogen bonds. Additional π–π interactions between neighboring thiophene and 2-thioxathiazolidin-4-one rings [intercentroid distance = 3.694 (2) Å] lead to the formation of a three-dimensional network.